Perceptions of online styles of news video production. Issue 2 (2nd April 2016) - Beatty, John
Abstract: This preliminary, exploratory study tested viewer reaction to three versions of the same news story manipulated to mimic the aesthetics and story arcs of 'Standard, ' 'YouTube' and 'MTV' styles of video. Participants were asked to rate the three versions on 13 semantic-differential items, as well as to discuss them in controlled focus groups. Results indicate that video news viewers do seem to have a preference for non-traditional types of news presentations online. Broadcasters and journalism faculty should become more familiar with new models of online news, such as the work of Philip DeFranco, who started out as an amateur, got his show adopted as an official YouTube™ channel, and was later signed to Discover Media.